2011
DOI: 10.1089/acm.2010.0176
|View full text |Cite
|
Sign up to set email alerts
|

Primary Massage Using One-Finger Twining Manipulation for Treatment of Infantile Muscular Torticollis

Abstract: PMTMOF produced more obvious curative treatment effects in infantile muscular torticollis than conventional tuina manipulation and could effectively shorten treatment time and avoid sequelae due to delayed healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Tuina is a well-recognized traditional Chinese massage therapy around the world and has innumerable clinical indications that are based on rigorous research evidence gathered through open and comparative randomized controlled clinical trials, systematic reviews and metaanalyses [1,5,8,13,[17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34]. Furthermore, most of clinical research in which Tuina is used either alone or in conjunction with other CAM or conventional medicine reported positive results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tuina is a well-recognized traditional Chinese massage therapy around the world and has innumerable clinical indications that are based on rigorous research evidence gathered through open and comparative randomized controlled clinical trials, systematic reviews and metaanalyses [1,5,8,13,[17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34]. Furthermore, most of clinical research in which Tuina is used either alone or in conjunction with other CAM or conventional medicine reported positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Tuina massage has many clinical applications and has been used safely in a variety of diseases with good outcome. Its clinical indications and contraindications are well recognized and reported in various studies [4,5,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Tuina is reported to have good safety profile, and most of the randomized controlled clinical trials along with systematic reviews and meta-analyses have reported no adverse effects [1,4,8,[13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other physical therapy modalities for the SCI treatment include massage of tight neck muscles and subcutaneous tissues which increases pain-free range of motion, joint mobilization, myofascial release, craniosacral therapies and therapeutic taping [13,24,25]. …”
Section: Treatment Physical Therapymentioning
confidence: 99%
“…Tuina therapy has unique advantages in clinical practice due to its features of green safety, precise curative effect, and high patient compliance. [ 20 , 21 ] In 2018, the APTA Pediatric Physical Therapy Society (APPT) supported the update of CMT's clinical practice guidelines (CPGs), and PTS also recommended manual traction as the preferred treatment for CMT[2]. In addition, in many published clinical studies on massage treatment of children with CMT, most studies have shown that massage is a reliable method of treating CMT.…”
Section: Introductionmentioning
confidence: 99%